Information and communication technology for agriculture in the People’s Republic of China - International Food Policy Research Institute; China Center for Agricultural Policy; Asian Development Bank; Valmonte-Santos, Rowena; Danessi, Lorena; Rosegrant, Mark W. (Asian Development Bank, 2019)
This report presents the findings of an assessment on the use of information and communication technology (ICT) to improve food production and distribution in the People’s Republic of China. The analysis focuses on e-commerce in rural areas of the country and provides policy recommendations to promote the use of ICT in the agricultural supply chain. The report documents the trends in ICT application by farmers and its impact on income and livelihood. It also identifies the major constraints to and enabling factors for such ICT applications.